2012
DOI: 10.2478/v10181-011-0135-3
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical evaluation of expression of heat shock proteins HSP70 and HSP90 in mammary gland neoplasms in bitches

Abstract: Heat shock proteins have essential roles in a number of pathophysiologic conditions including carcinogenesis and represent a group of novel molecular markers in cancer management.The aim of this study was to investigate heat shock protein expression in correlation with other neoplasm traits such as: histological type, differentiation grade, proliferative activity, estrogenic receptor expression, and cyclooxygenase-2 and p53 proteins. Material for the investigation comprised 133 tumors of the mammary gland coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 27 publications
2
14
0
Order By: Relevance
“…Our results support the findings of Badowska-Kozakiewicz and Malicka (2012) who reported that the expression of Hsp70 was the lowest in grade III canine mammary carcinomas.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Our results support the findings of Badowska-Kozakiewicz and Malicka (2012) who reported that the expression of Hsp70 was the lowest in grade III canine mammary carcinomas.…”
Section: Discussionsupporting
confidence: 83%
“…Moreover, the highest con- centration of these parameters was observed in malignant tumours. There are some reports that the level of Hsp70 expression is significantly elevated in canine mammary tumours (Kumaraguruparan et al, 2006;Romanucci et al, 2006;Badowska-Kozakiewicz and Malicka, 2012); however, there is no information on the concentration of Hsp70 in canine mammary tumours and non-tumorous mammary gland tissues. This fact makes it impossible to compare our results with those reported by other authors.…”
Section: Discussionmentioning
confidence: 99%
“…Molecular targets have been investigated to elucidate prognosis or the pathways of tumorigenesis such as CA15.3 and LDH (Campos et al, 2012), Snail (Im et al, 2012), cyclooxygenase-2 (Millanta et al, 2006a), heat-shock proteins (Badowska-Kozakiewicz, 2012;Romanucci et al, 2006), VEGF (Millanta et al, 2006b), p53, BRCA1, c-erbB-2 (Singer et al, 2012, antiapoptotic and proapoptotic proteins (Lana et al, 2007), β-catenin, E-cadherin and adenomatous polyposis coli protein (APC) (Restucci et al, 2007), and connexin (Torres et al, 2005), as well as several proliferation markers such as proliferating cell nuclear antigen (PCNA) and Ki-67 (Lana et al, 2007). Immunocytochemical Ki-67 marker and erythropoietin receptor expression seem to be useful to identify malignant canine tumors and patient poor outcome (Zuccari et al, 2004;Sfacteria et al, 2005).…”
Section: Neoplasiamentioning
confidence: 99%
“…Limitations of the current study include the lack of availability of a species‐specific positive control and that normal equine tissue was obtained from cadaveric globes. Equine mammary tumors are exceedingly rare, limiting access to an established positive control tissue in the horse . One previous study used the primary antibody utilized in this study to evaluate HSP70 expression in equine small intestine; however, the positive control in their staining protocol included human mammary carcinoma .…”
Section: Discussionmentioning
confidence: 99%